Resonant spread wave function in parabolic potential - Mazmanishvili, А.S. (Вопросы атомной науки и техники, 2019)
In this paper, we consider the parabolic potential, which as a whole is subject to dipole or quadrupole action (parametric resonance), which periodically changes with time, and the dynamics of the wave function of a particle. Based on the solutions found for the nonstationary Schrödinger equation, algorithms for calculating the dynamics of the wave function are constructed. The evolution of the wave function of a particle is analyzed. Asymptotic solutions of the equation of motion are given, using which the main characteristics of the wave packet are obtained. For selected types of potential perturbations, examples of the evolution of the wave function are given. Розглянуто параболічний потенціал, який як ціле схильний дипольному або квадрупольному впливу (параметричному резонансу), що періодично змінюється з плином часу, і динаміка хвильової функції частинки в ньому. На основі отриманих розв’язків нестаціонарного рівняння Шредінгера побудовані алгоритми розрахунку динаміки хвильової функції. Проаналізовано еволюцію хвильової функції частинки. Наведено асимптотичні рішення рівняння руху, за допомогою яких отримані основні характеристики хвильового пакета. Для обраних видів збурення потенціалу наведені приклади еволюції хвильової функції. Рассмотрен параболический потенциал, который как целое подвержен дипольному или квадрупольному воздействию (параметрическому резонансу), периодически меняющемуся с течением времени, и динамика волновой функции частицы в нем. На основе найденных решений нестационарного уравнения Шредингера построены алгоритмы расчета динамики волновой функции. Проанализирована эволюция волновой функции частицы. Приведены асимптотические решения уравнения движения, с помощью которых получены основные характеристики волнового пакета. Для выбранных видов возмущения потенциала приведены примеры эволюции волновой функции.